1996
DOI: 10.1164/ajrccm.154.6.8970385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interleukin-2 and cyclosporin A on pathologic features in Mycoplasma pneumonia.

Abstract: To elucidate the immunopathologic mechanisms of Mycoplasma pneumonia, the effects of interleukin-2 (IL-2) and cyclosporin A (CYA) on Mycoplasma pneumonia in mice were investigated. Mice were intranasally inoculated with Mycoplasma pulmonis (M. pul) and treated with IL-2, CYA, or minocycline (MINO) every day between Days 3 and 9. They were killed at Days 7, 14, or 21 after the inoculation. Cell-mediated immunity (CMI) of the host was assessed by delayed-type hypersensitivity (DTH) to sheep red blood cells (SRBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…IL-2 treatment enhanced the level of CMI and, simultaneously, exacerbated peribronchial lymphocyte infiltration and accumulation of macrophages at the ends of bronchioles; these pathological lesions were mimicking nodular opacities on CT of human MP. In contrast, CyA treatment depressed CMI, reduced peribronchial lymphocyte infiltration and exacerbated intra-alveolar inflammatory cell accumulation; these pathological changes may correspond to airspace consolidation on CT of human MP [18]. These findings supported the suggestion that the pathological pattern of lung lesions in MP might reflect the level of host CMI.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…IL-2 treatment enhanced the level of CMI and, simultaneously, exacerbated peribronchial lymphocyte infiltration and accumulation of macrophages at the ends of bronchioles; these pathological lesions were mimicking nodular opacities on CT of human MP. In contrast, CyA treatment depressed CMI, reduced peribronchial lymphocyte infiltration and exacerbated intra-alveolar inflammatory cell accumulation; these pathological changes may correspond to airspace consolidation on CT of human MP [18]. These findings supported the suggestion that the pathological pattern of lung lesions in MP might reflect the level of host CMI.…”
Section: Discussionsupporting
confidence: 67%
“…These pathological findings mimic those of a mouse mycoplasma model. We previously reported [18] the effect of interleukin-2 (IL-2) as a T-cell activator and cyclosporin A (CyA) as a T-cell selective suppressor on pulmonary lesions in such an animal model of mycoplasma infection. IL-2 treatment enhanced the level of CMI and, simultaneously, exacerbated peribronchial lymphocyte infiltration and accumulation of macrophages at the ends of bronchioles; these pathological lesions were mimicking nodular opacities on CT of human MP.…”
Section: Discussionmentioning
confidence: 99%
“…Among a number of cytokines reported to be associated with the pathomechanism of M. pneumoniae pneumonia, the author and coworkers have demonstrated that the macrophage-derived cytokines interleukin-18 and interleukin-8 play significant roles in the development of pneumonia and are directly related to disease severity [Narita et al, 2000[Narita et al, , 2001aTanaka et al, 2002]. Interleukin-18 is an immune regulatory cytokine that functions as an activator of T cells and a subsequent cascade of T helper-1 and T helper-2 type cytokines [Tanaka et al, 1996]. Interleulin-8 is an inflammatory cytokine and functions as an activator of neutrophils.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…As regards the presence of pneumonia in relation to the development of extrapulmonary diseases, the author and coworkers have found, using polymerase chain reaction methodology [Narita et al, 1992], that the genome of M. pneumoniae can be detected more frequently in serum from patients without pneumonia than in serum from patients with pneumonia [Narita et al, 1996]. This means that pneumonia, which is a consequence of the local host immune response occurring on the respiratory surface, plays an important role as a kind of fire-wall preventing dissemination of the organism beyond the respiratory tract [Cartner et al, 1998;Tanaka et al, 1996]. In this regard, it is important to note that directtype extrapulmonary manifestations not infrequently occur in the absence of pneumonia, which is a hallmark of mycoplasmal infecti o n .…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Researchers have reported that the cell-mediated immune response of the host, specifically through the function of Th1-type cytokines, has a critical role in the development of clinical manifestations and pathologic features of M. pneumoniae infection (11,12). More recently, it was reported that interleukin-18 (IL-18), a regulatory cytokine for Th1-type cytokines, plays an important role in pulmonary disease manifestation due to M. pneumoniae (5).…”
mentioning
confidence: 99%